2010
DOI: 10.1002/jnr.22410
|View full text |Cite
|
Sign up to set email alerts
|

Immunodeficiency reduces neural stem/progenitor cell apoptosis and enhances neurogenesis in the cerebral cortex after stroke

Abstract: Acute inflammation in the poststroke period exacerbates neuronal damage and stimulates reparative mechanisms, including neurogenesis. However, only a small fraction of neural stem/progenitor cells survives. In this report, by using a highly reproducible model of cortical infarction in SCID mice, we examined the effects of immunodeficiency on reduction of brain injury, survival of neural stem/progenitor cells, and functional recovery. Subsequently, the contribution of T lymphocytes to neurogenesis was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 36 publications
7
74
0
2
Order By: Relevance
“…However, the projecting pyramidal cortical neurons forming long-distance neuronal circuitry have been derived from these progenitor cells without much success, although a recent publication has demonstrated that ES cell-derived NSCs can differentiate into pyramidal cells that integrate into the adult poststroke cortex [11]. Although it would still be challenging to accomplish cortical neurogenesis after permanent ischemic stroke in vivo, we have shown that adequate support of iNSPCs in the in-vivo environment of the poststroke cortex (e.g., regulation of endothelial cells [7,9] and inflammatory cells [8]) could promote the proliferation of iNSPCs and enhance neurogenesis and cortical functional recovery.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, the projecting pyramidal cortical neurons forming long-distance neuronal circuitry have been derived from these progenitor cells without much success, although a recent publication has demonstrated that ES cell-derived NSCs can differentiate into pyramidal cells that integrate into the adult poststroke cortex [11]. Although it would still be challenging to accomplish cortical neurogenesis after permanent ischemic stroke in vivo, we have shown that adequate support of iNSPCs in the in-vivo environment of the poststroke cortex (e.g., regulation of endothelial cells [7,9] and inflammatory cells [8]) could promote the proliferation of iNSPCs and enhance neurogenesis and cortical functional recovery.…”
Section: Discussionmentioning
confidence: 84%
“…Previously, we demonstrated that immunodeficiency reduces neural stem/progenitor cell apoptosis and enhances neurogenesis in the cerebral cortex after stroke [8]. In this study, to determine cell proliferation in vivo, 7-week-old male SCID mice were injected with 5-bromo-2-deoxyuridinine (BrdU) to visualize regenerating neurons.…”
Section: Cell Proliferation Assessmentmentioning
confidence: 99%
“…Данный эффект воспроизводился при переносе спленоцитов или CD4 + T-клеток от толерантных мышей интактным животным [4]. Позитивный эффект Тreg может быть обусловлен не только их иммунорегуляторной активностью, направлен-ной на подавление воспалительного процесса, но и стимулирующим влиянием на стволовые клет-ки, поскольку деплеция Тreg сопровождается ос-лаблением нейрогенеза [104]. Другим механиз-мом Тreg может быть стимулирующее действие этих клеток на постишемическую неоваскуляри-зацию [141].…”
Section: адаптивный иммунный ответunclassified
“…Notably, similar to the healthy conditions, defined subpopulations of T cells contribute to modulate germinal niche functioning at early stages after injury. Removal of the whole CD4+ T cell population results in increased precursor/neuroblast generation few days after stroke, while depletion of the only Treg lymphocytes suppresses neurogenesis and reduces functional recovery (Saino et al, 2010). In contrast, promotion of Treg homing to the ischemic brain enhances NSC and neuroblast survival (Ishibashi et al, 2009).…”
Section: Immune System Regulation Of Germinal Niche Functioning Aftermentioning
confidence: 99%
“…In contrast, promotion of Treg homing to the ischemic brain enhances NSC and neuroblast survival (Ishibashi et al, 2009). At variance with non-pathological conditions, post-injury T cell effects appear to modulate pro-inflammatory cytokine secretion by activated endothelial cells rather than being mediated by microglial functions (Saino et al, 2010;Ishibashi et al, 2009). …”
Section: Immune System Regulation Of Germinal Niche Functioning Aftermentioning
confidence: 99%